Clinical Outcomes Associated With His-Purkinje System Pacing vs. Biventricular Pacing, in Cardiac Resynchronization Therapy: A Meta-Analysis - Gui, Yang; Ye, Lifang; Wu, Liuyang; Mai, Haohui; Yan, Qiqi; Wang, Lihong (Frontiers in Cardiovascular Medicine, 2022)
Aims His-Purkinje system pacing has recently emerged as an alternative to biventricular pacing (BIVP) in cardiac resynchronization therapy (CRT). The aim of this study was to conduct a meta-analysis comparing the clinical outcomes associated with His-Purkinje system pacing (HPSP) vs. BIVP in patients with heart failure. There is also a comparison of clinical outcomes of His-bundle pacing (HBP) and left bundle branch pacing (LBBP) in the His-Purkinje system. Methods We searched the Cochrane Library, Embase, and PubMed, for studies published between January 2010 and October 2021 that compared the clinical outcomes associated with HPSP vs. BIVP and HBP vs. LBBP in HPSP in patients who underwent CRT. The pacing threshold, R-wave amplitudes, QRS duration, New York Heart Association functional (NYHA), left ventricular ejection fraction (LVEF), and LV end-diastolic diameter (LVEDD) of heart failure, at follow-up, were extracted and summarized for meta-analysis. Results A total of 18 studies and 1517 patients were included in our analysis. After a follow-up period of 9.3 ± 5.4 months, the HPSP was found to be associated with shorter QRS duration in the CRT population compared to that in the BIVP (SMD, −1.17; 95% CI, −1.56 to −0.78; P < 0.00001; I2 = 74%). No statistical difference was verified between HBP and LBBP on QRS duration (SMD, 0.04; 95% CI, −0.32 to 0.40; P = 0.82; I2 = 84%). In the comparison of HPSP and BIVP, the LBBP subgroup showed improved LVEF (SMD, 0.67; 95% CI, 0.42–0.91; P < 0.00001; I2 = 0%), shorter LVEDD (SMD, 0.59; 95% CI, 0.93–0.26; P = 0.0005; I2 = 0%), and higher New York Heart Association functional class (SMD, −0.65; 95% CI, −0.86 to −0.43; P < 0.00001; I2 = 45%). In terms of pacing threshold and R-wave amplitude clinical outcomes, LBBP has a lower pacing threshold (SMD, 1.25; 95% CI, 1.12–1.39; P < 0.00001; I2 = 47%) and higher R-wave amplitude (MD, −7.88; 95% CI, −8.46 to −7.31; P < 0.00001; I2 = 8%) performance compared to HBP. Conclusion Our meta-analysis showed that the HPSP produced higher LVEF, shorter QRS duration, and higher NYHA functional class in the CRT population than the BIVP as observed on follow-up. LBBP has a lower pacing threshold and higher R-wave amplitude. HPSP may be a new and promising alternative to BIVP in the future.